Should 'Moral Taint' Be a Factor in Police Technology Procurement? The Case of Cellebrite. - Harkin, Diarmaid; Molnar, Adam; Onik, Md Mehedi Hassan; Panagiotopoulos, Vas (British Journal of Criminology, 2026)
Police increasingly experiment with new capabilities provided by external technology companies. Using technology sourced from the private sector can lead to more effective and efficient operations, but also creates a range of dilemmas based on the suitability and accountability of how the technology is implemented. This paper uses the concept of 'moral taint' to explore how controversies surrounding companies that the Police rely on should influence the procurement and use of those technologies. Using the example of Cellebrite, a company that sells digital forensics tools but has a range of alarming connections to human rights abuses, it is argued that Police could suffer from 'moral taint' of association with such a company and that this should be a factor in procurement and deployment. It is outlined that Police procurement of new technology requires stronger accountability and tougher oversight, specifically the introduction of standards around the moral suitability of companies that are engaged.